The interplay of systemic atrial and ventricular function in patients with transposition of the great arteries after arterial switch operation. (8th February 2021) - Schoeber, A; Jerosch-Herold, M; Wegner, P; Voges, I; Gabbert, D; Pham, HM; Scheewe, J; Kramer, HH; Rickers, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: The role of systemic atrial (LA) function and its interplay with the systemic ventricle (LV) in patients with transposition of the great arteries (TGA) after arterial switch operation (ASO) is currently not well defined. Purpose: Investigate the role of LA function and its interplay with the LV. Methods: Between 2007 and 2018 patients with TGA corrected by ASO and control patients of comparable age, sex, height but without known cardiovascular disease were included in this prospective single centre analysis of 3 Tesla cardiac magnetic resonance cine imaging studies of atrial and ventricular function. Additionally, in TGA patients extracellular volume fraction (ECV) was assessed by T1 mapping and global longitudinal strain (GLS) by feature tracking. Results: Overall, 81 TGA (16.3 [IQR 10.5-21.2] years, 32% female) and 30 control patients (11.9 [IQR 8.7-22.5] years, 63% female) were included in the current analysis. TGA patients had smaller LA maximum volume index, and reduced total atrial and conduit volume emptying. This resulted in a reduced LA reservoir and conduit function compared to controls. In TGA, a higher LA active/conduit and active/total ratio indicated impaired passive filling of the LV. (Table 1) The median ECV was 28.3% (IQR 25.8-33.9) and the median GLS -24.2% (IQR -28.6- -20.4) in TGA patients. LA reservoir (Fig. 1A), conduit and contractile function showed a negative correlation with GLS (r=-0.470, p < 0.001, r=-0.270, p = 0.022 and r=-0.257, p = 0.030, respectively). Interestingly, the LA active/conduit ratio (Fig. 1B) and the active/total ratio showed a positive correlation with ECV (r = 0.418, p = 0.002 and r = 0.339, p = 0.013, respectively). Conclusion: Impaired LA function is frequent among patients with TGA following ASO. The impairment of LA function is linked to both LV dysfunction and fibrosis.